Как преобразовать данное выражение в дробь 1/х*(х+1)+1/(х+1)*(х+2)+...+1/(х+99)*(х+100)
Как преобразовать данное выражение в дробь 1/х*(х+1)+1/(х+1)*(х+2)+...+1/(х+99)*(х+100)
Ответ(ы) на вопрос:
Гость
[latex] \frac{1}{x(x+1)} + \frac{1}{(x+1)(x+2)} + ...+\frac{1}{(x+99)(x+100)} =\\\\=( \frac{1}{x} - \frac{1}{x+1} )+( \frac{1}{x+1} - \frac{1}{x+2} )+...+ (\frac{1}{x+99} - \frac{1}{x+100})=\\\\= \frac{1}{x} - \frac{1}{x+100} = \frac{x+100-x}{x(x+100)} = \frac{100}{x(x+100)} [/latex]
Не нашли ответ?
Похожие вопросы